OPTIMALISASI DAKWAH DI ERA MODERN MELALUI MEDIA SOSIAL: NOVITA LESTARI - Lestari, Novita (Qawwam : The Leader's Writing, 2024)
This journal discusses the role and strategy of optimizing preaching (dakwah) through social media, particularly in the context of the millennial generation. The modern era, dominated by social media, compels speakers to adapt preaching methods to be more effective and relevant. The goal of preaching remains to ensure understanding and implementation of religious teachings by the audience (mad'u). This literature study employs a descriptive analysis approach with a focus on social media as the main tool for preaching. Social media facilitates two-way interaction, accelerates message dissemination, and fosters creativity in delivering religious content. Optimizing preaching is achieved through the utilization of information and communication technology, especially through mass media and social media. The influence of Islam on social media emphasizes the importance of ijtihad (independent reasoning) by preachers in adapting Islamic messages to formats suitable for these platforms. The article also highlights the challenges of preaching in the modern era, particularly in addressing the communication preferences and lifestyles of the millennial generation, who tend to be online. By integrating religious messages with social media platforms, preaching can reach a broader and more diverse audience without geographical limitations. In conclusion, the optimal approach to preaching in the current era requires mastery of social media as the primary means of disseminating religious messages, especially to reach the millennial generation, which is the main focus in this digital age.